The Problem of Social Knowledge in Contemporary Social Epistemology: Two Approaches - Rimkutė, Audronė (Problemos, 2004)
The article analyses how in one of the fields of contemporary epistemology – social epistemology – the social dimension of knowledge is theorized. There are discussed two strategies of the “socialisation” of epistemology: the investigation of the social factors, which can influence knowledge in the sense of true belief, in the field of epistemological investigation; and the definition of knowledge in social terms, as collectively accepted or institutionalised belief. The article examines the inner consistency of these two approaches and the perspectives for the epistemology that they set up. The first strategy is represented by the veritistic theory of Alvin I. Goldman. Social epistemology is only one part of his theory, which investigates and assesses social factors in terms of their impact on the truth-values of agents’ belief. The way how Goldman distinguishes social and individual part of his theory indicates that he interprets social dimension as the “extrinsic” and “acquired”, and contrasts it with individual dimension, which is “intrinsic” and “native”. In other words, his knowing agent is an individual “cognitive mechanism”, and only his received “input” is social. The article argues that this interpretation of the social is too narrow for social epistemology, because it hinders the incorporation of the problems concerned with the collective nature of knowledge production and the problem of significant knowledge. The second part of the article discusses the conception, which takes the second way of epistemology’s “socialisation” – the sociologistic social epistemology of Steve Fuller. Knowledge is conceived here as institutionalised belief, and epistemology as defined as knowledge economics and as science policy. The article argues that these two versions of Fuller’s theory are incompatible. Additionally, sociologistic concept of knowledge is not very suitable for knowledge economics, because it narrows its work to already institutionalised knowledge and says nothing about new knowledge. At the same time, sociologistic concept of knowledge is redundant for science policy, because some of Fuller’s proposals for science democratisation would be better grounded, if they invoked the realistic concept of science. So contemporary social epistemology vacillates meantime between two extremities: the individualistic concept of knowledge, which doesn’t help to solve the problems of collective knowledge production, and sociologistic one, which reduces knowledge seeking to social actions and therefore can’t provide base for the adequate knowledge and science policy.